171 Older people, alcohol and safety issues at home – the perspective of home care workers. (1st September 2016) - Koivula, Riitta; Vilkko, Anni; Tigerstedt, Christoffer; Kuussaari, Kristiina; Pajala, Satu
Abstract : Background: Finland is a rapidly ageing society. The Finnish ageing policy prioritises older people living at home. Alcohol use of older people has become more common. Heavy drinking in particular leads to the need of increasing daily assistance and care. This paper discusses the challenging social situations of daily work of home care workers visiting alcohol consuming older people in their homes. This study, called "Ageing, alcohol and needs for services in home care" (2014–2015), is a part of the larger project "Harms to others from drinking: effects on health, wellbeing and the burden to society". Methods: The data consists of 13 thematic interviews with home care workers (n = 10) and their supervisors (n = 3). The interviews were conducted in one home care district in the metropolitan area in Finland. Results: When making their home visits home care workers have to handle challenging safety issues, such as alcohol-drug interactions, injury prevention and their own safety at work. Home care workers encounter unpredictable situations where they for safety reasons cannot fulfil their professional intentions. Conclusions: Home care workers are in need of further training about special skills to manage alcohol-related safety questions. Collaboration crossing professional and sectoral boundaries should be created to help those older people who are at the risk of alcohol-related safety issues. Further research is needed on older peoples' alcohol use from the point of view of home care workers.